Introduction to ordinary differential equations - Saperstone, Stephen H. (Pacific Grove, California : Brooks/Cole Publishing Company, 1998)
Integrated applications and models, along with graphical and numerical procedures motivate and explain mathematical techniques in this volume. Numerical methods are covered early in the course. Contents: 1. Introduction. 2. First-Order ODEs. 3. Geometry and Approximation of Solutions. 4. Linear Second-Order ODEs. 5. Additional Topics in Linear Seond-Order ODEs. 6. Laplace Transforms. 7. Series Solutions of Linear Second-Order ODEs. 8. Linear Two-Dimensional Systems of ODEs. 9. Nonlinear Two-Dimensional Systems of ODEs.
Keywords: DIFFERENTIAL EQUATIONS